2015
DOI: 10.1002/pssb.201552296
|View full text |Cite
|
Sign up to set email alerts
|

Transport, magnetic and vibrational properties of chemically exfoliated few-layer graphene

Abstract: Abstractauthoren We study the vibrational, magnetic and transport properties of Few Layer Graphene (FLG) using Raman and electron spin resonance spectroscopy and microwave conductivity measurements. FLG samples were produced using wet chemical exfoliation with different post‐processing, namely ultrasound treatment, shear mixing, and magnetic stirring. Raman spectroscopy shows a low intensity D mode which attests a high sample quality. The G mode is present at 1580 cm−1 as expected for graphene. The 2D mode con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 73 publications
(106 reference statements)
3
17
0
Order By: Relevance
“…Chemical exfoliation was finalized using different mechanical routes: ultrasound sonication, shear mixing and mechanical stirring. In a previous study, we showed that mechanical processing affects the material quality of final product 67 . Further details of the sample preparation are described in Ref.…”
Section: Methodsmentioning
confidence: 95%
“…Chemical exfoliation was finalized using different mechanical routes: ultrasound sonication, shear mixing and mechanical stirring. In a previous study, we showed that mechanical processing affects the material quality of final product 67 . Further details of the sample preparation are described in Ref.…”
Section: Methodsmentioning
confidence: 95%
“…Prior to in situ measurements, the undoped FLG was heated to 400 °C for 30 min in high vacuum (2 × 10 −6 mbar) to remove any residual solvents. It was shown previously in the previous studies [ 28,29 ] that this does not affect the morphology of the starting FLG.…”
Section: Methods and Sample Preparationmentioning
confidence: 62%
“…[25][26][27] Chemical exfoliation was finalized using ultrasound tip sonication, as it is known to produce the best quality. [28,29] The properties of the starting material are well characterized by atomic force microscopy and Raman spectroscopy, which revealed that the restacked FLG is also present in the sample. [29] The dominant portion (90%) of the material consists of five layers or less, including monolayer content.…”
Section: Methods and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations